4D Printing: 3D‐Printed Hydrogel Composites for Predictive Temporal (4D) Cellular Organizations and Patterned Biogenic Mineralization (Adv. Healthcare Mater. 1/2019). Issue 1 (10th January 2019) - McCracken, Joselle M.; Rauzan, Brittany M.; Kjellman, Jacob C. E.; Kandel, Mikhail E.; Liu, Yu Hao; Badea, Adina; Miller, Lou Ann; Rogers, Simon A.; Popescu, Gabriel; Nuzzo, Ralph G.
Abstract : In article number1800788, Ralph G. Nuzzo and co‐workers show micro‐scaffold hydrogels that are fabricated using the additive manufacturing technique of direct‐ink writing (DIW). The hydrogel compositions are optimized for multilayer printing and are used to tune growth compliance by directing the temporal dynamics and spatial distribution of cell attachment without the use of surface‐modifying treatments. Image courtesy of Joselle M. McCracken.